Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Please help serious answers only

Please Help Serious Answers Only class=

Sagot :

Answer:

22

Step-by-step explanation:

Substitute z = 6 into the expression

2z² - 8z - 2

= 2(6)² - 8(6) - 2

= 2(36) - 48 - 2

= 72 - 50

= 22